5D operando tomographic diffraction imaging of a catalyst bed. Issue 1 (December 2018) - Vamvakeros, A.; Jacques, S.; Di Michiel, M.; Matras, D.; Middelkoop, V.; Ismagilov, I.; Matus, E.; Kuznetsov, V.; Drnec, J.; Senecal, P.; Beale, A.
Abstract We report the results from the first 5D tomographic diffraction imaging experiment of a complex Ni–Pd/CeO2 –ZrO2 /Al2 O3 catalyst used for methane reforming. This five-dimensional (three spatial, one scattering and one dimension to denote time/imposed state) approach enabled us to track the chemical evolution of many particles across the catalyst bed and relate these changes to the gas environment that the particles experience. Rietveld analysis of some 2 × 106 diffraction patterns allowed us to extract heterogeneities in the catalyst from the Å to the nm and to the μm scale (3D maps corresponding to unit cell lattice parameters, crystallite sizes and phase distribution maps respectively) under different chemical environments. We are able to capture the evolution of the Ni-containing species and gain a more complete insight into the multiple roles of the CeO2 -ZrO2 promoters and the reasons behind the partial deactivation of the catalyst during partial oxidation of methane. Multi-scale chemical imaging holds the potential to revolutionize our understanding of the relationships between structure and functionality in complex catalytic materials. Here the authors report the results from the first 5D tomographic diffraction imaging experiment of a complex Ni – Pd/ CeO2 – ZrO2 / Al2 O3 catalyst used for methane reforming.